Analisis Logam Berat Timbel (Pb) di Low Emission Zone Kawasan Kota Tua Jakarta - Aninda Dian Lestari; Hernani Yulinawati; Endro Suswantoro (Jurnal Serambi Engineering, 2023)
AbstractIn an effort to improve air quality, the DKI Jakarta Provincial Government has implemented a Low Emission Zone (LEZ) in Kawasan Kota Tua Jakarta since 2021. Only pedestrians, bicycles, public transport, and specially marked vehicles can cross LEZ. The purpose of this study is to analyze the concentration of Pb in Kawasan Kota Tua Jakarta based on Ambient Air Quality Standard (BMUA). The research method used in this study is descriptive quantitative. Samples were taken using a portable High Volume Air Sampler and analyzed using Atomic Absorption Spectrophotometry Flame. Sampling was carried out on March 25–May 15, 2022 (7 days) during the morning, afternoon, and evening at 4 points, UPK Kota Tua (UPK), Jakarta History Museum (MSJ), Kota Tua Entrance (PMK) and Jakarta Kota Station (SJK) so that 84 samples were collected. The results showed that the Pb concentration was higher than BMUA PP 22/2021 (2µg/Nm3 for a 24-hour period) in PMK 4,343µg/Nm3 (Friday), SJK 2,080µg/Nm3 (Wednesday), and at every sampling point (2,055–3,094µg/Nm3) on Saturday-Sunday. In conclusion, there are Pb concentrations that have passed the BMUA at certain locations and days. The average concentration of Pb in locations outside the LEZ tends to be higher than in the LEZ locations. Keywords: ambien air, Kawasan Kota Tua Jakarta, low emission zone, high volume air sampler, atomic absorption spectrophotometry flame, lead.